2018
DOI: 10.1039/c7cy01890h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of catalytic activity of Pd-PVP colloid for direct H2O2synthesis from H2and O2in water with addition of 0.5 atom% Pt or Ir

Abstract: Atomically dispersed Pt or Ir atoms enhance H2O2 and H2O formation on Pd nano-particles leaving the H2O2 hydrogenation rate unchanged, while Ru, Rh, or Au atoms show little effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Enhanced productivity and selectivity were observed upon addition to Pd of another noble metal, more often Au [40][41][42][43][44][45][46]. It has also been demonstrated that the combination of Pd with Ir [47], Ag [48,49], and Pt [50] can improve both the productivity and the selectivity of the process. On the contrary, the presence of Rh and Ru increased H 2 O 2 decomposition activity of Pd catalysts [51].…”
Section: Effect Of Metal Promoters and Alloysmentioning
confidence: 98%
See 1 more Smart Citation
“…Enhanced productivity and selectivity were observed upon addition to Pd of another noble metal, more often Au [40][41][42][43][44][45][46]. It has also been demonstrated that the combination of Pd with Ir [47], Ag [48,49], and Pt [50] can improve both the productivity and the selectivity of the process. On the contrary, the presence of Rh and Ru increased H 2 O 2 decomposition activity of Pd catalysts [51].…”
Section: Effect Of Metal Promoters and Alloysmentioning
confidence: 98%
“…Also by DFT calculations, Deguchi et al [47] found that the adsorption energies of H 2 , O 2 , H 2 O 2 , and HBr were larger on coordinatively more unsaturated sites (such as corners and edges) than on more saturated sites such as a {111} facet. The energy profiles of the H 2 + O 2 reaction suggested that H 2 O 2 would be smoothly produced on more saturated sites such as the {111} facet.…”
Section: Influence Of Surface Morphologymentioning
confidence: 99%
“…Edwards et al . were the first to report increased catalytic activity towards H 2 O 2 formation when alloying Au and Pd, building on these initial findings subsequent investigation of Pd‐based, bi‐ and tri‐metallic catalysts for the direct synthesis reaction with numerous combinations of catalysts since reported, including; Pd−Pt, Pd−Ru, Pd−Rh,, Pd‐Ir and Au−Pd‐Pt ,…”
Section: The Role Of Secondary Metals In the Direct Synthesis Of H2o2mentioning
confidence: 99%
“…has investigated the effect of precious metal (Au, Pt, Ru, Rh and Ir) addition to a Pd‐polyvinylpyrrolidone colloid, with dramatic enhancements being observed with the addition of very low (0.5 at. %) concentrations of Pt or Ir doubling the formation rate of H 2 O 2 . Kinetic analysis, supported by DFT studies, indicated that the high H 2 activating abilities of Pt and Ir were responsible for the enhanced H 2 O 2 synthesis reaciton rate, while the subsequent H 2 O 2 hydrogenation rate remained fairly constant with Pt and Ir incorporation, indicating that the H 2 * activated on Ir or Pt played little role in the degradation of H 2 O 2 .…”
Section: The Role Of Secondary Metals In the Direct Synthesis Of H2o2mentioning
confidence: 99%
“…35 Recent studies by Deguchi et al have shown that a range of bimetallic colloidal particles stabilised with PVP, including Pd-Ir and Pd-Pt, can be active catalystshowever the role of the polymer additive in all these cases has not been explicitly addressed. 36 Recently we demonstrated that using colloidal AuPd nanoparticles stabilised with PVP, it was possible to achieve selective oxidation of methane to methanol at 25-50°C with O 2 incorporation using H 2 O 2 as an initiator. 37 A significant result in this study showed that the background H 2 O 2 decomposition rate was minimal for unsupported colloidal AuPd-PVP particles at 50°C, allowing the radical reaction process to propagate rather than terminate; however the H 2 O 2 decomposition rate increased significantly when then the same particles were supported on TiO 2 making this an ineffective catalyst.…”
Section: Introductionmentioning
confidence: 99%